Network pharmacological prediction and molecular docking analysis of the combination of Atractylodes macrocephala Koidz. and Paeonia lactiflora Pall. in the treatment of functional constipation and its verification. Issue 2 (22nd April 2022) - Meng, Yuxiao; Li, Xiaojun; Wang, Xiaoting; Zhang, Lu; Guan, Jiaqi
Abstract: Background: We aimed to reveal the mechanism of functional constipation in the treatment of Atractylodes macrocephala Koidz. (AMK) and Paeonia lactiflora Pall. (PLP). Methods: The main active ingredients of AMK and PLP were screened by the Traditional Chinese Medicine Systems Pharmacology (TCMSP) platform. A database of functional constipation targets was established by GeneCard and OMIM. An "ingredient‐target" network map was constructed with Cytoscape software (version 3.7.1), and molecular docking analysis was performed on the components and genes with the highest scores. The rats in the normal group were given saline, and those in the other groups were given 10 mg/kg diphenoxylate once a day for 14 days. The serum and intestinal tissue levels of adenosine monophosphate (cAMP), protein kinase A (PKA), and adenylyl cyclase (AC) of the rats and aquaporin (AQP)1, AQP3, and AQP8 were measured. Results: AMK and PLP had a significant role in the regulation of targets in the treatment of functional constipation. After treatment with AMK, PLP, or mosapride, the serum and intestinal tissue levels of AC, cAMP, and PKA were significantly downregulated. Groups receiving AMK and PLP or mosapride exhibited a reduction in the level of AQP1, AQP3, and AQP8 to varying degrees. Conclusion: Molecular docking analysis revealed that AMK and PLP had a significant role in the regulation of targets in the treatment of functional constipation. Studies have confirmed that AMK and PLP can also affect AC, cAMP, and PKA. AC, cAMP, and PKA in model rats were significantly downregulated. AQP expression is closely related to AC, cAMP, and PKA. AMK and PLP can reduce the expression of AQP1, AQP3, and AQP9 in the colon of constipated rats. Abstract : The intersection indicates a gene shared by two or three substances. The Venn diagAMK of the visualized relationship between PLP, AMK and functional constipation shows that PLP and AMK contain 30 common chemical constituents, PLP and functional constipation contain 76 common chemical constituents and AMK and functional constipation contain 24 common chemical constituents of which the three together contain 21 kinds of chemical compositions. To organize the active ingredients and targets of the two drugs, the components and targets of the two traditional Chinese medicines were imported into Cytoscape 3.7.1 to construct the basic adjustment and visualization of the traditional Chinese medicine compound‐target network.